KEDUDUKAN JAMINAN DALAM KONTRAK SYARIAH: KAJIAN NORMATIF TERHADAP AKAD IJARAH MUNTAHIYAH BITTAMLIK - Widiana, Sri; Khasanah, Maulidatul; Fadhilah, Aula Nisa'ul; Kurniawan, Rangga Fajar; Musadad, Ahmad (Jurnal Ilmiah Advokasi, 2025)
Collateral in the Ijarah Muntahiyah Bittamlik (IMBT) contract has an important role in providing legal certainty and protecting the rights of the parties involved. This research analyzes the position of collateral in IMBT from the perspective of Islamic law and regulations in Indonesia with a normative approach. Based on the study, collateral in IMBT can be in the form of temporary ownership by the renter or additional collateral to avoid default, as long as it is in accordance with sharia principles. Regulations in Indonesia, such as the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and the rules of the Financial Services Authority (OJK), have accommodated guarantees in IMBT to ensure compliance with Islamic law and provide legal protection for Islamic financial institutions and customers. This study also compares the application of guarantees in IMBT with other contracts, such as Musyarakah Mutanaqisah (MMQ), which shows differences in the legal aspects of guarantees. The results of this study aim to strengthen regulations and education for Islamic financial industry players so that the implementation of IMBT remains in accordance with sharia principles. Thus, the guarantee in the IMBT contract can increase public confidence in Islamic banking and strengthen the stability of the sharia-based economy.Keywords: Guarantee, Sharia Contract, Ijarah Muntahiyah Bittamlik.